Репрезентация дихотомии духа и тела в культуре античной Греции - Тесленко, Татьяна Викторовна (Грани, Днипро, 2017)
RU: Трансформации концептов духа и тела как основных бинарных оппозиций западноевропейской философии и культуры находятся в центре внимания ученых-постмодернистов, философов, социологов, психологов, литературоведов, теоретиков гендера и т.д., представляющих, как правило, междисциплинарный модус научного исследования. Введение постструктуралистами принципа телесности повлекло за собой переосмысление многих понятий, с использованием которых различие между «внутренним» и «внешним» практически снималось. С другой стороны, поскольку в русле герменевтической интерпретации любой текст находится в непрерывно изменяющемся контексте исторической ситуации, проблема повествования как взаимоотношения между «историей», нарративом и жизнью, занимая одно из ключевых мест в теории постмодернизма, представляется концептуально важной в научном анализе философии и культуры любой эпохи, тем более, мира древней Греции, в недрах которой произошел «разрыв» духа и плоти, оказавший огромное влияние на всю последующую классическую философию. Гомер, собрав в «Иллиаде» и «Одиссее» этические нормы и предписания поведения своего времени, видел своих героев воплощением телесного совершенства, в то же время его фундаментальная ментальность продолжает оказывать свое влияние и сегодня: в «Иллиаде» ключевые слова – состязание миф, аргумент, убеждение; в «Одиссее» – море, свобода, приключения, богатство, знание. Однако, в целом, гомеровский человек характеризуется как «симфония» различных голосов: человек у Гомера обладает не «телом», но множеством различных органов и частей тела. Слияние взаимоотношения «внутреннего» и «внешнего» в мире человека античной Греции получает воплощение в трагедиях Софокла, Эсхила, Еврипида, которые создали не только художественные образы, оказавшие огромное влияние на всю последующую литературную традицию, но и были «философами на сцене», «оракулами» этических идей, – как публичных, так и личных. И здесь важно подчеркнуть: конфликт бинарных сил аполлонического и дионисейского начал, являющийся «первичным конфликтом» всей западной культуры, в творениях Эсхила и Софокла представляет собой трансформацию, ведущую к их слиянию, у Еврипида – отчетливая репрезентация рационализма, осознание дуальности рационального и иррационального, тела и духа.

UK: Трансформації концептів духу і тіла як основних бінарних опозицій західноєвропейської філософії та культури знаходяться в центрі уваги вчених-постмодерністів, філософів, соціологів, психологів, літературознавців, теоретиків гендеру і т.д., що представляють, як правило, міждисциплінарний модус наукового дослідження. Введення постструктуралістами принципу тілесності спричинило переосмислення багатьох понять, з використанням яких відмінність між «внутрішнім» і «зовнішнім» практично знімалося. З іншого боку, оскільки в руслі герменевтичної інтерпретації будь-який текст знаходиться в безперервно змінному контексті історичної ситуації, проблема оповіді як взаємовідносини між «історією», наративом і життям, займаючи одне з ключових місць в теорії постмодернізму, представляється концептуально важливою в науковому аналізі філософії та культури будь-якої епохи, тим більше, світу древньої Греції, в надрах якої стався «розрив» духу і плоті, що зробив величезний вплив на всю подальшу класичну філософію. Гомер, зібравши в «Ілліаді» і «Одіссеї» етичні норми та приписи поведінки свого часу, бачив своїх героїв втіленням тілесної досконалості, в той же час його фундаментальна ментальність продовжує надавати свій вплив і сьогодні: в «Іліаді» ключові слова – змагання міф, аргумент, переконання; в «Одіссеї» – море, свобода, пригоди, багатство, знання. Однак, в цілому, гомерівська людина характеризується як «симфонія» різних голосів: людина у Гомера володіє не «тілом», а безліччю різних органів і частин тіла. Злиття взаємин «внутрішнього» і «зовнішнього» в світі людини античної Греції отримує втілення в трагедії Софокла, Есхіла, Евріпіда, які створили не тільки художні образи, що зробили величезний вплив на всю подальшу літературну традицію, але були «філософами на сцені», «оракулами» етичних ідей, – як публічних, так і особистих. І тут важливо підкреслити: конфлікт бінарних сил аполлонічного і діонісейського начал, що є «первинним конфліктом» всієї західної культури, в творіннях Есхіла і Софокла є трансформацією, що веде до їх злиття, в Евріпіда – виразна репрезентація раціоналізму, усвідомлення дуальності раціонального і ірраціонального, тіла і духу.

EN: The transformations of the concepts of spirit and body being the main dichotomy of the Western philosophers are in the focus of postmodern theorists – philosophers, literary antics sociologists, gender researchers, etc., thus they are usually representing the inter-disciplinary modus of postmodern scientific analyses. The introduction of the principle of corporeality by poststructuralists caused the rethinking of many classical concepts, which in its turn, led to the elimination of differences between «the Outer» «the Inner». On the other hand, as in hermeneutics any text is considered as being put in the continuously changing context of history and culture, the problem of narration is understood as the interrelation between «a history», «a narrative» and life in the broad meaning of this notion. The latter is considered as the conceptually significant in the analysis of the philosophy and the culture of any epoch, and in the particularly context, the culture of Ancient Greece is of paramount importance. Moreover, it gave birth to the disruption of soul and body of spirit and flesh and, thus, influenced greatly the subsequent development of the Western classical philosophy. Homer, having collected the ethical norms and prescription for the behavior of the Greeks in «Illiad» and «Odyssey», depicted his heroes as an embodiment of the physical perfection. At the same time, Homer’s fundamental mentality is still influential at the beginning of the third millennium: in «Illiad» the key woods are contest, dispute, war, argument, persuasion; in «Odyssey» – freedom, adventure, wealth, knowledge. On the whole, the man of Homer is characterized as «a symphony of many voices». Homer’s man does not possess «the body», he possesses different organs and parts. However, the discovery of the body by Homer had great consequences: sexuality and sensuality are among the most valuable gifts of ancient Greece to the modern world. The complicated interrelations of «the Outer» and «the Inner» in the world of the Ancient Greece are represented in the tragedies of Aeschylus, Sophocle and Euripides. They created not only literary images that made bad enormous impact on the Western culture, they were «philosophers on the stage» teaching morality in both public and private spheres of life. In Aeschylus’s tragedies the most important problems of the opposition of the individual and the society are represented on the stage; Sophocle, who made the tragedy «go down from Heaven to the Earth» paid great attention to the man in his inner world transformations; Euripides, who described people as they were in their real lives, also connected his intentions with presentation of the inner world of human beings, both man and women. Especially interesting is the role of women in Euripides’ tragedies: the most remarkable examples of self-sacrifice are given by Euripides’ heroines. The Greek woman in Euripides’ tragedies is a morally mature human being, she is self-conscious, and her attitude to the world is critical. Special attention should be paid to the consideration of the Appolonian and Dionysian forces which are declared to be «the primary conflict» of the Western culture. Being a philosophical and literary dichotomy in Sophocles’ and Euripides’ tragedies, they represent the transformations, which led to their confluence. The corporal sensuality of the Ancient Greece literature, promoting the transformations of sensuality into art, nowadays is still one of the key narratives of Western culture, both in its high and low versions.
Репрезентація дихотомії духу і тіла в культурі античної Греції
The Representation of the Dichotomy of Spirit and Body in the Culture of Ancient Greece
Т. Тесленко: ORCID 0000-0002-5810-3569
Keywords: античность; нарратив; постмодернизм; субъект; телесность; текст; античність; наратив; постмодернізм; суб’єкт; тілесність; antiquity; narrative; postmodernism; subject; corporeality; text; КЕМ